Return migration, entrepreneurship and development in rural Kosova - Lumnije Kadriu (Kosova Anthropologica)
Return migration has become very prominent a pattern in the migration trajectories of peoples’ mobility and thus increasingly researched, revealing a myriad of nuances and experiences. Mostly, the motive for emigration is based on the desire and goal to achieve a success which will prove fruitful upon return. However, the return is faced with different challenges which were/are being under the scrutiny of return migration theoretical explanations. Although Kosova is primarily known as a country of emigration due to its turbulent political history and ongoing economic challenges there are evidenced cases of voluntary return migration. In this paper I will bring experiences of several low-skilled returned emigrants in their villages of origin who established businesses upon return that resulted with certain degree of development and upward social status mobility at personal and communal level. The return of low-skilled workers in rural areas may be among the most challenging returns if considered limited opportunities these areas usually provide. However, new dynamics, especially in tourism potential, are emerging in rural areas. The cases in this paper are quite unique and serve as an illustration of different individual agencies of migrants used as strategy of return.